2014
DOI: 10.1371/journal.pone.0088382
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Glucocorticoid Sensitivity in Early Life Shape the Risk of Epithelial Barrier Defect in Maternal-Deprived Rats

Abstract: Glucocorticoids (GC) contribute to human intestine ontogeny and accelerate gut barrier development in preparation to birth. Rat gut is immature at birth, and high intestinal GC sensitivity during the first two weeks of life resembles that of premature infants. This makes suckling rats a model to investigate postpartum impact of maternal separation (MS)-associated GC release in preterm babies, and whether GC sensitivity may shape MS effects in immature gut. A 4 hours-MS applied once at postnatal day (PND)10 enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 51 publications
4
68
0
3
Order By: Relevance
“…Other studies performed in male rats indicate an alteration of the intestinal barrier at weaning in the maternal separation model 23 that was detected by the significant increase of colonic short-circuit current and horseradish peroxidase flux along with increased intestinal permeability that was still maintained in adulthood. 6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies performed in male rats indicate an alteration of the intestinal barrier at weaning in the maternal separation model 23 that was detected by the significant increase of colonic short-circuit current and horseradish peroxidase flux along with increased intestinal permeability that was still maintained in adulthood. 6,34 Glucocorticoids play a role in the increased intestinal permeability induced by a short acute maternal separation stress in PND10 pups 17 but not in adult rats subjected to repeated maternal separation. 36,37 In the present study, we found no correlation between corticosterone plasma levels and intestinal permeability at weaning, either in LNS or BMS models, suggesting that glucocorticoids are not involved in the mechanisms contributing to the altered permeability.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 Samples were centrifuged (10 minutes, 2500 g) and plasma was stored at -80 o C until assay. Plasma corticosterone concentration was determined by enzyme immunoassay (Cayman Chemical, Ann Arbor, MI, USA) according to the manufacturer's instructions.…”
Section: Plasma Corticosterone Determinationmentioning
confidence: 99%
See 3 more Smart Citations